2004
DOI: 10.1007/s10350-004-0560-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lymphatic Micrometastases in Patients With Stages I and II Colorectal Cancer: Impact on Five-Year Survival

Abstract: The presence of micrometastases in patients with Stages I and II colorectal cancer seems not to have any impact on cancer-specific survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…Relevant articles were identified through a PUBMED search using the terms "colorectal cancer," "lymph nodes," and "micrometastasis," Additional articles were identified through careful review of the referenced articles from these initially identified publications. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, the reviewed studies consistently evaluate the pN0 LN from stage 1 and stage 2 CRC patients (in some studies referred to as Dukes A and B) for the presence of occult metastases. The following aspects were considered with regard to each study: i) size of study including number of stage 1 and 2 patients and percentage of rectal cancer patients; ii) method used for occult metastasis detection; iii) potential for sampling error (includes sectioning analysis, number of slides, sections, and levels of sections per LN, and number of LNs reviewed per patient); iv) quality control of original pathological diag- nosis; v) percentage of patients that were upstaged; vi) mean or median follow-up (5-year survival and recurrence data are ideal); and vii) antibodies and/or markers used for IHC or PCR.…”
Section: Search Methods and Article Selectionmentioning
confidence: 99%
“…Relevant articles were identified through a PUBMED search using the terms "colorectal cancer," "lymph nodes," and "micrometastasis," Additional articles were identified through careful review of the referenced articles from these initially identified publications. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, the reviewed studies consistently evaluate the pN0 LN from stage 1 and stage 2 CRC patients (in some studies referred to as Dukes A and B) for the presence of occult metastases. The following aspects were considered with regard to each study: i) size of study including number of stage 1 and 2 patients and percentage of rectal cancer patients; ii) method used for occult metastasis detection; iii) potential for sampling error (includes sectioning analysis, number of slides, sections, and levels of sections per LN, and number of LNs reviewed per patient); iv) quality control of original pathological diag- nosis; v) percentage of patients that were upstaged; vi) mean or median follow-up (5-year survival and recurrence data are ideal); and vii) antibodies and/or markers used for IHC or PCR.…”
Section: Search Methods and Article Selectionmentioning
confidence: 99%
“…With IHC and molecular genetics methods, occult tumor cells in regional lymph nodes are detected in 25% to 50% of patients with node-negative colorectal cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Because up to 25% of patients with node-negative colorectal cancer ultimately die as a result of disease relapse, occult cancer metastasis has been suspected as a potential marker for systemic spread of tumor cells (1).…”
Section: Introductionmentioning
confidence: 99%
“…Because up to 25% of patients with node-negative colorectal cancer ultimately die as a result of disease relapse, occult cancer metastasis has been suspected as a potential marker for systemic spread of tumor cells (1). However, the prognostic value of molecular tumor cell detection in patients with node-negative colorectal cancer has remained uncertain because of lack of evidence from prospective studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of micrometastases (MCMs) within LNs that are not detected by conventional hematoxylin and eosin (H-E) staining provides a possible explanation for this discrepancy. However, although the presence of LN MCMs in CRC patients has been investigated, no consensus has been reached regarding the prognostic significance of this finding (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%